KARAKTERISASI PADI BERAS MERAH ENSALANG YANG TELAH DIRADIASI DENGAN SINAR GAMMA COBALT-60 300 GRAY DI LAHAN SAWAH - Saputra, Djaka Dwi (Jurnal Sains Pertanian Equator, 2019)
The aim of this study was to determine the morphological and agronomical characters of Ensalang mutant rice, which had been radiated by Gamma Cobalt-60 300 Gray and posible any differencial to wild type. This research was carried out on tidal rice fields belonging to BBI, at Sungai Kakap. The research conducted in November 2017- Mei 2018 ( ± 6 months). Research is direct observation of plants. Planted using 4 : 1 planting system with 25 x 25 cm spacing. The seedling used are 21 days old. Seedling planted singlely. The variables are various characters of plants, namely morphological and agronomical characters of rice. The number of plant populations observed was 100 plants. The results of observations of each character from each plant are very diverse both in terms of quantitative and qualitative. From the comparison with the original species planted on the same land, there was a slight difference in the characteristics of seedling height, leaf ligule length, leaf ligule shape, stem segment color, panicle type, seed width, seed thickness, panicle release, grain fertility , weights of 100 seeds of plants.Keywords : agronomy, ensalang rice, morphology, red rice, tides, gamma rays.